Iron-bearing halloysite for wetland remediation: Curvature-controlled oxidation pathways and ecological implications - Zihan Shu; Zhiyan Feng; Chencheng Qin; Aoqiang Shu; Limei Shi; Miao Li; Zichen Shangguan; Wenyan Zhou; Ying Li; Xingzhong Yuan; Hou Wang (Water Research, 2026)

Vibration attenuation of rigid foldable origami-inspired metamaterials - Haizhou Shi; Kai Zhang; Xiangbing Liu; Chen Gao; Zichen Deng (Engineering Structures, 2026)

Preparation and properties of an in-situ sealing and water retention double-network gel for inhibiting coal spontaneous combustion - Jiangle Wu; Caiping Wang; Jun Deng; Yang Xiao; Yi Lu; Zichen Shi; Zujin Bai; Jiuxiao Lu (Journal of Environmental Chemical Engineering, 2026)

Regulating the hydrogen transfer pathways for electrochemical nitrate-to-ammonia at industrial current density - Zeyu Li; Zichen Shi; Chu Zhang; Chunshuang Yan; Shijie Chen; Nian Ran; Chenhui Yin; Qingyu Yan; Chade Lv (Science Bulletin, 2026)

Efficient persulfate activation via a novel layered porous biochar enhanced with nano-zero-valent iron loading and synergistic sulfidation modification: Performance and mechanism - Lei Shen; Zichen Qin; Yuanding Shi; Yan Li; Pengyao Guo; Jinwei Zhang; Yijun Shen; Chun Yang; Yuchen Zeng; Dongxiao Sun; Zhiqiang Dong; Lei Ding (Journal of Water Process Engineering, 2026)

A hybrid method coupling physical process-driven model with generative deep learning for probabilistic flood forecasting - Xuesong Yang; Bin Xu; Jingwen Liu; Junliang Jin; Ran Mo; Xinrong Wang; Zichen Ren; Yao Liu; Yuchen Shi; Qisheng Zhou; Ping-an Zhong (Journal of Hydrology, 2026)

Managing street-tree health under rapid urbanization: Relative roles of street context and root-zone conditions in a subtropical city - Wenting Wang; Min Wu; Hai Yan; Ying Chen; Zichen Zhao; Lin Zhu; Jiangnan Shi; Renwu Wu; Fan Yang; Zhiyi Bao (Journal of Environmental Management, 2026)

Schnurri-3 inhibitor-modified 3D-printed hierarchical porous scaffold promoted vascularized bone regeneration via enhanced BMSC-EC crosstalk - Suru Liu; Shichong Qiao; Zichen Tang; Xiaomeng Zhang; Yulin Yang; Xindi Wei; Junyu Shi; Yingxin Gu; Meifei Lian; Hongchang Lai (Chemical Engineering Journal, 2026)

SV wave scattering by a circular-arc depositional canyon in an unsaturated site - Tianyu Shi; Qiang Ma; Zichen Zhang (Soil Dynamics and Earthquake Engineering, 2026)

Spring extreme heat in the Indochina Peninsula enhances the prediction skill of summer precipitation in Central China - Yihua He; Wei Lou; Cheng Sun; Menghao Dong; Zichen Song; Linfeng Shi; Yibing Tong (Atmospheric Research, 2026)

Seasonal dynamics of Gulf Stream–Kuroshio SST coupling: the role of hemispheric atmospheric teleconnections - Menghao Dong; Cheng Sun; Linfeng Shi; Wei Lou; Zichen Song; Yihua He; Yibing Tong (Climate Dynamics, 2026)

Air temperature differences and view factor influences between sidewalks and roadways in urban streets: A case study in Hangzhou, China - Zichen Zhao; Hai Yan; Huaizhen Zhu; Xinge Nan; Renwu Wu; Wenting Wang; Wei Yang; Lin Zhu; Jiangnan Shi; Fan Yang; Zhiyi Bao (Building and Environment, 2026)

Changes in persistent anticyclonic circulation across Eurasian continent and its linkage with extreme heatwaves - Yibing Tong; Cheng Sun; Wei Lou; Menghao Dong; Linfeng Shi; Zichen Song; Yihua He (Global and Planetary Change, 2026)

Robust station-keeping for Halo orbits via auxiliary-controller-independent Lyapunov-based model predictive control - Zhitong Yu; Haibin Shang; Zichen Zhao; Yue Dong; Lusha Shi (Advances in Space Research, 2026)

Enhanced efficiency of bacteria-algae symbiotic biofilm reactors in treating coal chemical wastewater: Mechanisms and microbial dynamics - Jingxin Shi; Yuanyuan Yang; Zichen Zhu; Shengyang Li; Haifeng Zhuang (Journal of Environmental Chemical Engineering, 2025)

Potential buffering capacity of naturally distributed carbonate minerals against future rises in atmospheric CO2 and coastal acidification: the Yellow Sea and three major estuaries in China - Wenting Shi; Weidong Zhai; Shu Yang; Congcong Guo; Zichen Liu; Hongmei Chen (Marine Environmental Research, 2025)

Abrupt vapor pressure deficit changes over Northeast Asia during 1990s linked to combined Mediterranean-Pacific SST shifts - Zichen Song; Cheng Sun; Dong Xiao; Menghao Dong; Wei Lou; Linfeng Shi (Atmospheric Research, 2025)

Global teleconnection of concurrent dry and wet events revealed by climate network - Menghao Dong; Cheng Sun; Wei Lou; Linfeng Shi; Zichen Song; Yihua He; Yibing Tong (Climate Dynamics, 2025)

Response of heterocyst differentiation of Dolichospermum to different forms of nitrogen deficiency - Zichen Liu; Fazhi Xie; Liya Wang; Li Yu; Xiaoli Shi; Zhen Yang; Min Zhang (Harmful Algae, 2024)

High-level and -yield orotic acid production in Escherichia coli through systematic modular engineering and “Chaos to Order Cycles” fermentation - Changgeng Li; Tangen Shi; Wenjing Fan; Meng Yuan; Lanxiao Li; Zichen Yu; Zhichao Chen; Qingyang Xu (Bioresource Technology, 2024)

Glutamine metabolism in fluorosis: Integrated metabolomics and transcriptomics analysis - Yue Ba; Shu Niu; Zichen Feng; Shuo Yang; Shuiyuan Yu; Chaofan Shi; Xuecheng Jiao; Guoyu Zhou; Fangfang Yu (Science of The Total Environment, 2024)

Unravelling spatiotemporal patterns in global sea surface temperatures with dynamic mode decomposition - Menghao Dong; Cheng Sun; Tian Wei; Zijing Guo; Wei Lou; Zichen Song; Linfeng Shi (International Journal of Climatology, 2024)
Extracting global sea surface temperature (SST) patterns is essential for understanding climate variability in both regional and global perspective. Traditional methods, limited by assumptions of orthogonality, hinder our ability to fully capture the dynamics of global SST, particularly in the complex Pacific basin. This study introduces dynamic mode decomposition (DMD), a powerful method from fluid dynamics, to extract global SST patterns since 1900. Our analysis shows that DMD successfully captures well‐known patterns like global warming and the Atlantic Multidecadal Oscillation (AMO). More importantly, it reveals three Pacific SST modes that are spatially non‐orthogonal but exhibit distinct characteristics. Spectral analysis shows that these Pacific modes have distinct periodicities: Pacific Multi‐decadal Mode (PMDM, ~50 years), Quasi‐decadal Mode (PQDM, 8–16 years) and Interannual Mode (PIAM, 2–8 years). This highlights DMD's strength in not only capturing known patterns but also separating modes with similar spatial features but unique dynamics. Further analysis reveals significant differences in their impacts on global air temperature. During positive phases, all three modes induce tropical warming, with PIAM exerting the strongest influence and PMDM the weakest. In the Northern Hemisphere, both PQDM and PIAM drive mid‐latitude cooling and high‐latitude warming, with a more pronounced effect from PQDM. PMDM, in contrast, triggers widespread cooling across the Northern extratropics. In the Southern Hemisphere, PMDM's influence on temperature exhibits a distinct latitudinal banding pattern. PIAM and PQDM, on the other hand, exhibit a regionalized impact, primarily concentrated in the Amundsen and Ross Seas, with PQDM's influence extending to the Antarctic continent.

Novel Coumarins Derivatives for A. baumannii Lung Infection Developed by High-Throughput Screening and Reinforcement Learning - Jing Li; Zhou Lu; Liuchang Wang; Huiqing Shi; Bixin Chu; Yingwei Qu; Zichen Ye; Di Qu (Journal of Neuroimmune Pharmacology, 2024)
With the increasing resistance of Acinetobacter baumannii ( A. baumannii ) to antibiotics, researchers have turned their attention to the development of new antimicrobial agents. Among them, coumarin-based heterocycles have attracted much attention due to their unique biological activities, especially in the field of antibacterial infection. In this study, a series of coumarin derivatives were synthesized and screened for their bactericidal activities (Ren et al. 2018; Salehian et al. 2021). The inhibitory activities of these compounds on bacterial strains were evaluated, and the related mechanism of the new compounds was explored. Firstly, the MIC values and bacterial growth curves were measured after compound treatment to evaluate the antibacterial activity in vitro. Then, the in vivo antibacterial activities of the new compounds were assessed on A. baumannii -infected mice by determining the mice survival rates, counting bacterial CFU numbers, measuring inflammatory cytokine levels, and histopathology analysis. In addition, the ROS levels in the bacterial cells were measured with DCFH-DA detection kit. Furthermore, the potential target and detailed mechanism of the new compounds during infection disease therapy were predicted and evidenced with molecular docking. After that, ADMET characteristic prediction was completed, and novel, synthesizable, drug-effective molecules were optimized with reinforcement learning study based on the probed compound as a training template. The interaction between the selected structures and target proteins was further evidenced with molecular docking. This series of innovative studies provides important theoretical and experimental data for the development of new anti- A. baumannii infection drugs.

Interhemispheric propagation of seasonal sea surface temperature fluctuations over the western Pacific in CMIP6 - Tian Wei; Cheng Sun; Zijing Guo; Wei Lou; Zichen Song; Linfeng Shi; Menghao Dong (International Journal of Climatology, 2024)
Interannual sea surface temperature (SST) variability in the western Pacific is a critical research topic in climate change, as it can significantly impact regional and global weather patterns. Previous observational studies have shown that SST in the southwestern Pacific (SWP) can effectively serve as a precursor signal for SST in the western tropical Pacific (WTP). In this study, we evaluate and compare the modelling capabilities of 32 CMIP6 models to simulate the relationship between SWP and WTP SST. The results indicate that while some CMIP6 models can simulate the spatial connection and physical processes between the SWP and WTP, there are significant intermodel differences. Specifically, the models that best simulate the cross‐equatorial propagation of SWP SST anomalies are those that accurately simulate the cross‐equatorial wind anomalies induced by SWP SST anomalies, highlighting the key role of wind‐evaporation‐SST feedback in SST propagation. Further analysis reveals that the intermodel spread in cross‐equatorial SST propagation is attributable to model biases in simulating climatological SST and wind speed. Models with warm climatological equatorial SST and strong wind speeds provide favourable conditions for the cross‐equatorial propagation of SWP‐related SST anomalies towards the north. Warm SST and strong inter‐season wind speeds near the equator facilitate the northward propagation of the SWP warm signal, leading to increased warming in the WTP.

Cheap and easily separate Cs(I) and Rb(I) from high salty solution by forming RbCs–MgHCF - Kang Li; Junjie Xie; Zhuonan Shi; Changli Min; Zichen Yin; Ruixin Ma; Shina Li (Journal of Cleaner Production, 2023)

Risk factors for recurrent positive results of the nucleic acid amplification test for COVID-19 patients: a retrospective study - Wanwan Yi; Xuan Long; Jin Liu; LiShuai Shi; Zichen Chen; Jing Yang; Ziyu Yang; Zhongwei Lv; Hengwei Fan (Human Cell, 2021)
Positive retests of COVID-19 represent a public health concern because of the increased risk of transmission. This study explored whether factors other than the nucleic acid amplification test (NAAT) contribute to positive retest results. Patients with COVID-19 admitted to the Guanggu district of the Hubei Maternal and Child Health Hospital between February 17 and March 28, 2020, were retrospectively included. The patients were grouped into the negative ( n = 133) and positive ( n = 51) retest groups. The results showed that the proportion of patients presenting with cough was higher ( P < 0.001) and the proportion of patients with dyspnea was lower ( P = 0.018) in the positive than in the negative retest group. The positive retest group showed shorter durations between symptom onset and hospitalization ( P < 0.001) and symptom onset and the first positive NAAT ( P = 0.033). The positive retest group had higher basophil counts ( P = 0.023) and direct bilirubin ( P = 0.032) and chlorine concentrations ( P = 0.023) but lower potassium concentrations ( P = 0.001) than the negative retest group. Multivariable regression analysis showed that coughing (OR = 7.59, 95% CI 2.28–25.32, P = 0.001) and serum chloride concentrations (OR = 1.38, 95% CI 1.08–1.77, P = 0.010) were independently associated with a positive retest result. Coughing and serum chloride concentrations were independent risk factors for positive NAAT retest results. Patients with a hospital stay of < 2 weeks or a short incubation period should stay in isolation and be monitored to reduce transmission. These results could help identify patients who require closer surveillance.

Characterization and genome sequencing of a novel T7-like lytic phage, kpssk3, infecting carbapenem-resistant Klebsiella pneumoniae - Yunlong Shi; Yu Chen; Zichen Yang; Yulong Zhang; Bo You; Xinzhu Liu; Ping Chen; Meixi Liu; Cheng Zhang; Xiaoqiang Luo; Yajie Chen; Zhiqiang Yuan; et al. (Archives of Virology, 2020)

Characterization and genome annotation of a newly detected bacteriophage infecting multidrug-resistant Acinetobacter baumannii - Zichen Yang; Xinzhu Liu; Yunlong Shi; Supeng Yin; Wei Shen; Jing Chen; Yu Chen; Yajie Chen; Bo You; Yali Gong; Xiaoqiang Luo; Cheng Zhang; et al. (Archives of Virology, 2019)

P2Y6 Receptor-Mediated Microglial Phagocytosis in Radiation-Induced Brain Injury - Yongteng Xu; Weihan Hu; Yimin Liu; Pengfei Xu; Zichen Li; Rong Wu; Xiaolei Shi; Yamei Tang (Molecular Neurobiology, 2016)